Efficacy of Reinforced Stapler Versus Hand-sewn Closure of the Pancreatic Stump During Pure Laparoscopic Distal Pancreatectomy to Reduce Pancreatic Fistula. Issue 2 (20th April 2023) - Murata, Yasuhiro; Maeda, Koki; Ito, Takahiro; Gyoten, Kazuyuki; Hayasaki, Aoi; Iizawa, Yusuke; Fujii, Takehiro; Tanemura, Akihiro; Kuriyama, Naohisa; Kishiwada, Masashi; Mizuno, Shugo
Abstract : Background: Laparoscopic distal pancreatectomy (L-DP) is the standard procedure for treating left-sided pancreatic tumors. Stapler closure of the pancreas is the preferred method for L-DP; however, postoperative pancreatic fistula (POPF) remains a challenging problem. The present study aimed to compare the surgical outcomes of staple closure using a reinforcing stapler (RS) and transection using an ultrasonic dissector followed by hand-sewn (HS) closure in a fish-mouth manner in pure L-DP and to determine independent perioperative risk factors for clinically relevant postoperative pancreatic fistula (CR-POPF). Patients and Methods: Among the 85 patients who underwent pure L-DP between February 2011 and August 2021, 80 of whom the pancreatic stump was closed with RS (n = 59) or HS (n = 21) were retrospectively investigated. Associations between potential risk factors and POPF were assessed using univariate analysis. The factors, of which the P value was determined to be <0.1 by univariate analysis, were entered into a multivariate regression analysis to ascertain independent predictive factors. Results: The surgery time and estimated blood loss were not significantly different between the two groups. Overall, 13 patients (16.3%) developed CR-POPF ( B = 12 and C = 1). The rate of CR-POPF was lower in RS than in HS; however, the difference was not statistically significant (RS vs HS: 11.9% vs 28.9%, P = 0.092). Consistent with the results for CR-POPF, the rate of Clavien-Dindo IIIa or more postoperative complications and the length of hospital stay were also not significantly different between the two groups (RS vs HS: 10.2, 12% vs 14.3%, 14 d). In the univariate analysis of risk factors for CR-POPF, the pancreatic thickness at the transection site, procedure for stump closure, and estimated blood loss were associated with a significantly higher rate of CR-POPF. The multivariate analysis revealed that the pancreatic thickness at the transection site (cutoff: 12 mm) was the only independent risk factor for CR-POPF (odds ratio: 6.5l, 95% CI: 1.4-30.4, P = 0.018). The rate of CR-POPF was much lower in RS than in HS for pancreatic thickness <12 mm (RS vs HS: 4.1% vs 28.6%), whereas that was rather higher in RS than in HS for pancreatic thickness ≥12 mm (RS vs HS: 50% vs 28.6%). Conclusions: RS closure was superior to HS closure for pancreatic thickness <12 mm and for prevention of CR-POPF after pure L-DP. It is necessary to seek more reliable procedures for pancreatic stump closure in patients with a pancreatic thickness of ≥12 mm.